Depression and Sexual Stigma Are Associated With Cardiometabolic Risk Among Sexual and Gender Minorities Living With HIV in Nigeria. (1st January 2023) - Adebajo, Sylvia B.; Adebiyi, Ruxton; Chama, John; Bello, Segun; Ononaku, Uche; Aka, Abayomi; Lai, Shenghan; Baral, Stefan D.; Dyer, Typhanye V.; Crowell, Trevor A.; Nowak, Rebecca G.; Charurat, Man; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: People living with HIV are vulnerable to cardiometabolic diseases. We assessed the prevalence of cardiometabolic risk factors (CMRF) and associations with sexual stigma and depression among sexual and gender minorities (SGM) in Abuja and Lagos, Nigeria. Methods: The TRUST/RV368 study enrolled SGM between March 2013 and February 2020. Participants were assessed for depression, sexual stigma, and CMRF. Robust multinomial logistic regression was used to estimate adjusted odds ratio (aORs) and 95% confidence intervals (CIs) for associations of depression, sexual stigma, and other factors with increasing numbers of CMRF. Results: Among 761 SGM, the mean age was 25.0 ± 6.0 years; 580 (76%) identified as cisgender men, 641 (84%) had ≥1 CMRF, 355 (47%) had mild–severe depression, and 405 (53%) reported moderate–high sexual stigma. Compared with individuals without depression, those with mild (aOR 8.28; 95% CI: 4.18 to 16.40) or moderate–severe depression (aOR 41.69; 95% CI: 9.60 to 181.04) were more likely to have 3–5 CMRF. Individuals with medium (aOR 3.17; 95% CI: 1.79 to 5.61) and high sexual stigma (aOR 14.42; 95% CI: 2.88 to 72.29) compared with those with low sexual stigma were more likely to have 3–5 CMRF. Participants age 25–34 years were less likely to have 3–5 CMRF (aOR 0.41; 95% CI: 0.23 to 0.73) compared with participants age younger than 25 years. Conclusion: CMRF increased with severity of depression and sexual stigma, potentially predisposing SGM living with HIV to cardiometabolic diseases. Integrating interventions that address depression and sexual stigma in HIV care programs for SGM may improve cardiometabolic outcomes.